Comparison of antibody production against aflatoxin B1 in goats and rabbits. - Gaur, P K (1980)
Antibody production against aflatoxin B1 was compared in three rabbits and one goat. Titers obtained were 20 times higher in the rabbits than in the goat. The goat antiserum appeared to have a higher degree of cross-reactivity for other aflatoxins and related metabolites than did the rabbit antiserum.